2016
DOI: 10.1002/aelm.201600254
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Multiferroic Material, Bi4Ti3O12·nBiFeO3 with Localized Magnetic Ordering Evaluated from Their Single Crystals

Abstract: Novel multiferroic materials have attracted increasing attention in recent years. Aurivillius bismuth‐layer structured Bi4Ti3O12·nBiFeO3 (BTFO: n = 1–3, 5) compounds with potential multiferroic properties are such a compound. However, the data on these BTFOs are ambigious, inconsistent, and incomplete. Therefore BTFOs were grown into single crystals for a systematic evaluation. Their crystal structures and microstructures show that intergrowth of layer structure occurs easily in this class of material. Their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The XRD patterns of the as-prepared film BFTO- n ( n = 1, 2, 3) indicated that the materials show a single Aurivillius phase. With the increase of n , the peaks at ∼30.3 and ∼32.8° shifted to the opposite direction, which is consistent with the results reported in the previous literature . Besides, the EDS patterns of Bi 4+ n Fe n Ti 3 O 12+3 n ( n = 1–4) are shown in Figure B in order to analyze the elemental content and distribution, and corresponding elemental analysis results are shown in Table S1 and Figure C, which proved that the atomic ratio of Bi, Ti, Fe, and O is almost identified with that added in the synthesis process.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The XRD patterns of the as-prepared film BFTO- n ( n = 1, 2, 3) indicated that the materials show a single Aurivillius phase. With the increase of n , the peaks at ∼30.3 and ∼32.8° shifted to the opposite direction, which is consistent with the results reported in the previous literature . Besides, the EDS patterns of Bi 4+ n Fe n Ti 3 O 12+3 n ( n = 1–4) are shown in Figure B in order to analyze the elemental content and distribution, and corresponding elemental analysis results are shown in Table S1 and Figure C, which proved that the atomic ratio of Bi, Ti, Fe, and O is almost identified with that added in the synthesis process.…”
Section: Resultssupporting
confidence: 89%
“…With the increase of n, the peaks at ∼30.3 and ∼32.8°shifted to the opposite direction, which is consistent with the results reported in the previous literature. 41 Besides, the EDS patterns of Bi 4+n Fe n Ti 3 O 12+3n (n = 1−4) are shown in Figure 1B in order to analyze the elemental content and distribution, and corresponding elemental analysis results are shown in Table S1 and Figure 1C, which proved that the atomic ratio of Bi, Ti, Fe, and O is almost identified with that added in the synthesis process. Further, elemental mapping patterns for BFTO-1 are presented in Figure 1D−H, which shows the uniform distribution of the elements Bi, Fe, Ti, and O.…”
Section: ■ Introductionmentioning
confidence: 88%
“…More importantly, this individual single-crystalline nanoplate can verify intrinsic FM and FE properties of Aurivillius-type BFTO-n compounds [59]. Apart from the nano-crystals, single crystals of the BFTO-n were grown by using modified micro-pulling down method [60]. The growth system uses mirror halogen lamps and a Pt tube, and the type of heater lamp, tube diameter, heating power, molten zone properties, and rotation speed are key factors and should be adjusted for different crystal types.…”
Section: Nanostructures and Single Crystalsmentioning
confidence: 99%
“…In the last decade, numerous pieces of research focused on the BFTO-n with integer n, for example, Bi 5 FeTi 3 O 15 , Bi 6 Fe 2 Ti 3 O 18 , and Bi 7 Fe 3 Ti 3 O 21 . The reported studies have mainly embodied two aspects: (i) doping ions into A-sites [19][20][21][22][23][24][25][26][27][28][29] and/or substituting magnetic transition ions into B-sites [30][31][32][33][34][35][36][37][38][39][40][41][42][43] inside the layered perovskite structure to realize a significant enhancement in the multiferroic performances, and (ii) controllable synthesis of materials in ceramics [44][45][46], thin films [47][48][49][50][51][52], nano-crystallines [53][54][55][56][57][58] and single crystals [59][60][61] to observe the growth process [62][63][64]…”
Section: Introductionmentioning
confidence: 99%
“…The Aurivillius layers (Bi 2 O 2 ) 2+ and distorted perovskite slabs produce great polarization in the structure . The most well‐known Aurivillius oxides are BiFeO 3 and Bi 4 Ti 3 O 12 . The combination between BiFeO 3 and Bi 4 Ti 3 O 12 results in different Aurivillius phases, which is denoted by Bi n+1 Fe n−3 Ti 3 O 3n+3 (n ≥ 4) .…”
Section: Introductionmentioning
confidence: 99%